ACL LENGTH IN PEDIATRIC POPULATIONS: AN MRI RETROSPECTIVE STUDY. Issue 4 (28th April 2020) - Tran, Emily P.; Chen, Anthony Y.; Dingel, Aleksei B.; Terhune, Bailey; Segovia, Nicole A.; Ganley, Theodore J.; Fabricant, Peter D.; Green, Daniel W.; Stavinoha, Tyler J.; Shea, Kevin G.
Background: Young athletes have the highest rates of primary and recurrent anterior cruciate ligament (ACL) tears, and recent research has identified graft diameter as a predictor of graft failure. Newer ACL reconstruction techniques have been developed to increase graft diameter and reduce re-rupture rates. Graft diameter can be modified based upon graft length, number of graft strands/configuration, and native ACL length. While the ACL has been well-studied in adult populations, there is limited research examining the ACL dimensional characteristics in a pediatric population. Appropriate preoperative anatomic dimensions may help surgeons plan for optimal graft length, diameter and bundle arrangement Purpose: To develop MRI-based predictors of native ACL graft length in pediatric populations and enhance preoperative planning to optimize graft length, strand configuration and graft diameter to lower the risk of recurrent ACL injury. Methods: One hundred and ten subjects were included from the STRIDE database (64 females and 46 males, median age 10 years, range 1-13 years). Our exclusion criteria were if the subjects had musculoskeletal diseases or history of knee injury. Using MRIs, researchers evaluated ACL length, sagittal and coronal inclination of the ACL, inclination and width of the intercondylar notch, depth and width of the femoral condyles, and the medial and lateral tibial slopes. Association between measurements, sex, and age were investigated using linear and multivariate regression models. Results: When examining the predictors for ACL length by sex, the best predictor (R⁁2 = 0.65) for female ACL lengths was the depth of the lateral femoral condyle taken in the sagittal view (p<0.001). Other predictors that were statistically significant (p < 0.005) were distal femoral condylar width (R⁁2 = 0.62), age (R⁁2 = 0.52), and coronal notch width (R⁁2 = 0.15). For males, the best predictor (R⁁2 = 0.70) of ACL length was the distal femoral condyle width as viewed coronally (p < 0.001). Other statistically significant predictors (p < 0.005) of male ACL lengths were lateral femoral condyle depth (R⁁2 = 0.62), age (R⁁2 = 0.48), and coronal notch width (R⁁2 = 0.20). Conclusion: When predicting the ACL length in pediatric populations, femoral condylar depth and width, and patient age may be valuable predictors for those undergoing ACL reconstructions. Surgical planning to maximizing graft diameter is contingent upon native ACL graft length, and the use of this information to optimize graft utilization may lower the rates of ACL graft failure in the highest risk pediatric populations. : Tables/Figures: Table 1.1. Predictors of ACL Length Figure 1.2. Figure 1.3.